Participation of Rural Women in Joint Forest Management: A Strategy for Sustainable Development - Bhutia, Karma Detsen; Debbarma, Raju (Indian Forester, 2017)
Forest resources are of great importance to the people residing in the vicinity of the forest areas as it provides means of livelihood and is deeply associated with socio-economic life of rural communities. More than 80% of geographical area of Sikkim state is cover by forest and it provides an important source of livelihood. In Sikkim, rural women play a vital role in sharing the household responsibilities and enjoy a significant position both in society and at home, but being a patriarchal form of society, land ownership has remained matter of concern. To examine the participation of rural women in JFM and their attitude towards forest and forest related activities, primary data was collected through household survey and focused group discussion was also conducted. The finding indicates that growing restriction on the traditional rights of women to access the forest resources has had an adverse impact on the livelihood of rural women. It has been found that during the plantation programme, women groups outnumbered the male population, which reflects that women are more involved in subsistence activities and value the conservation of forest resources. The study shows that despite the importance of women's role in forest management, i.e., JFMC, they have been marginalized.